A Cell‐Free Silk Fibroin Biomaterial Strategy Promotes In Situ Cartilage Regeneration Via Programmed Releases of Bioactive Molecules (Adv. Healthcare Mater. 1/2023). Issue 1 (2nd January 2023) - Mao, Zhinan; Bi, Xuewei; Wu, Chengai; Zheng, Yufeng; Shu, Xiong; Wu, Sujun; Guan, Juan; Ritchie, Robert O.
Abstract : In Situ Cartilage Repair In article 2201588 by Xiong Shu, Sujun Wu, Juan Guan, Juan Guan, and co‐workers, a cell‐free silk protein sponge is fitted on site of a cartilage defect. The in situ cartilage repair is assisted by programmed factors E7 and TGF‐ β 1, that trigger serial events of autologous stem cell homing, directed differentiation and chondrocyte proliferation.